REALISM AND COLONIALISM IN DANIEL DEFOE’S ROBINSON CRUSOE - Hasan, Mariwan; HamaSaeed, Awara (Universitas Islam Negeri Sunan Gunung Djati, 2022)
This study deals with realism in Defoe’s Robinson Crusoe. Realism in the study explained the straightforward treatment in life. Realism sheds light on the immediate, the specific actions and their verifiable consequences. Realism seeks a direct connection between representation and the subject. The study is aimed to interpret the actualities of any aspect of life, not restricted to subjective prejudice, idealism, or romantic color. First, an introduction is presented about Realism, which is comprehensively linked to the history of realism and its revolution. Then, the reasons that affected development of English novel will be explained in details. Moreover, we give an extensive emphasis on realism in English literature and describe the novel in 18th century. Then, characteristics of English novel is explained in details and definitions of realism according to a number of authors expressed then we talk about Daniel Defoe as the father of early English novel. Finally, Robinson Crusoe is analyzed and the most important themes of the novel such as colonialism and realism are shed light on to show the degree of similitude in the novel that drew the attention of its readers since the 18th century.Keywords: eighteenth century novel, early english novel, Daniel Defoe, Realism, Robinson Crusoe